Prevalence and associated factors of postpartum depression among women in putalibajar municipality - Sharma, Rakshya; Kaphle, Hari Prasad (Journal of Psychiatrists’ Association of Nepal, 2025)
Background: Postpartum depression (PPD) is the onset of a non-psychotic mood or mental disorder, which usually occurs among mothers, and it can persist for weeks or months after delivery. Although PPD has been widely studied globally, there is limited research in Nepal despite its significant impact on maternal health and child development. This study aims to identify the prevalence and factors associated with postpartum depression among women in Putalibajar municipality, Nepal. Methods: A community-based cross-sectional study was conducted in between October 2019 to March 2020 among 263 married women of the extended postpartum period in Putalibajar municipality, Gandaki Province, Nepal. Data were collected by face-to-face interviews via an interview schedule. The Edinburgh Postnatal Depression Scale (EPDS) was used to measure postpartum depression. Chi-square test was performed to assess the association between PPD and independent variables, and regression was used to assess the strength of association Results: The prevalence of postpartum depression was 10.6%. Women whose husbands consumed alcohol (AOR=5.582; CI 95%:1.514-20.581) and women who faced intimate partner violence during pregnancy (AOR=9.134; CI 95%:2.709-30.792) were more likely to develop postpartum depression. Conclusion: One out of ten women reported having postpartum depression. Husband’s alcohol consumption and intimate partner violence during pregnancy were associated with postpartum depression.